Removal of phenol from aqueous solution by absorption on yeast, saccharomyces cerevisiae - Moyo, Mambo; Mutare, Eusebia; Chigondo, Fidelis; Nyamunda, Benias C. (2016)
The aim of this study is to investigate the possibility of Saccharomyces cerevisiae as an alternative adsorbent for phenol removal from aqueous solution .The Saccharomyces cerevisiae was characterised by Brunauer Emmett Teller (BET) and Fourier transform (FT-IR). Adsorption properties of Saccharomyces cerevisiae towards phenol were systematically investigated, including pH effect, adsorbent dosage, contact time and initial concentration. The adsorption of phenol decreased with increasing pH. The experimental data were analysed by Langmuir and Freundlich models in order to describe the equilibrium isotherms. Equilibrium data fitted well to the Langmuir model with correlating constant (R2) higher than 0.99. The study showed that Saccharomyces cerevisiae could be used as a new and efficient adsorbent material for the removal of phenol from aqueous solution.